The role of a national system of innovation in facilitating development in South Africa from a comparative BRICS perspective - Sibhukwana, Andiswa (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The aim of the dissertation was to investigate whether the adoption of a national system of innovation has helped facilitate development in South Africa from a comparative BRICS perspective. South Africa has an expanding focus on science and technology, as per the Science and Technology White Paper (1996). There appeared to be innovation that had left out much of the citizenry. There continued to be poverty, inequality, and joblessness. The study aimed to understand how the NSI approach could be used to foster inclusive and transformative development. The study used a mixed-methods approach. The qualitative aspect of the research focused on an innovation and public policy study which assessed the various policies and initiatives implemented in each of the BRICS countries to drive innovation and foster development. The qualitative aspect of the study found that the innovation paradigm required governments to adopt a more holistic approach to public policy design and analysis. The quantitative aspect of the research focused on a trend, correlation, and regression analysis. The trend analysis revealed that China and Brazil increased their allocation of resources towards R&D compared to the other countries. Brazil is regarded as a social investment state, while China is a developmental state: this means the state plays an extraordinarily strong coordinative and financing role in the NSI. On the other hand, the correlation matrix for South Africa revealed a statistically significant positive linear association between various NSI indicators and human development. This suggested that the innovation benefits are trickling down to the general citizenry. In essence the study articulated key elements of the understanding of current and potential impacts of technological change in productivity and growth, employment and inequality that can be used for policy making.
Keywords: BRIC countries; Technological innovations Economic aspects -- South Africa; Economic development -- South Africa; Economics Mathematical models; Neoclassical school of economics; South Africa Economic conditions; South Africa Economic policy; National systems of innovation